2014
DOI: 10.1002/j.1556-6676.2014.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Use by Counselors in the United States: Implications for Policy and Practice

Abstract: Although assessment use is a professional activity recognized by every major counseling organization, little is known about which assessments are used in counseling. In this study, 926 respondents from a random national sample of counselors reported their use of personality, projective, career, intelligence/cognitive, educational/achievement, clinical/behavioral, and environmental/interpersonal tests. Test rankings by frequency of use and comparisons by type of counselor and type of test are reported. Implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 39 publications
(62 reference statements)
0
35
0
1
Order By: Relevance
“…The BDI-II is one of the most commonly used depression inventories used for clinical screening and outcome research (Muller & Erford, 2012;Peterson et al, 2014). The results of this meta-analysis of 144 studies exploring the psychometric characteristics of the BDI-II English version provide robust estimates of internal consistency for both clinical (α = .91, k = 56, n = 13,447) and nonclinical (α = .88, k = 43, n = 17,966) samples.…”
Section: Discussionmentioning
confidence: 97%
“…The BDI-II is one of the most commonly used depression inventories used for clinical screening and outcome research (Muller & Erford, 2012;Peterson et al, 2014). The results of this meta-analysis of 144 studies exploring the psychometric characteristics of the BDI-II English version provide robust estimates of internal consistency for both clinical (α = .91, k = 56, n = 13,447) and nonclinical (α = .88, k = 43, n = 17,966) samples.…”
Section: Discussionmentioning
confidence: 97%
“…The ease of administration and interpretation add to its utility as an instrument for practitioners wishing to differentiate between anxiety and depression. Furthermore, its low cost and ease of administration and interpretation add value to its use in counselor preparation programs (Neukrug et al, ; C. H. Peterson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although most appropriate for use with psychiatric outpatients 17 years and older, it has been used in research studies with both clinical and nonclinical samples. Among counselors, the BAI is reported to be the ninth most commonly used instrument (C. H. Peterson, Lomas, Neukrug, & Bonner, ). Similarly, Neukrug, Peterson, Bonner, and Lomas () reported that the BAI was the ninth most commonly taught instrument by counselor educators.…”
mentioning
confidence: 99%
“…A second study of assessment use by practitioners, except those in school and mental health areas, revealed the SDS was the third most frequently used assessment (Peterson, Lomas, Neukrug, & Bonner, 2014).…”
Section: Trainingmentioning
confidence: 99%